Screening for New Surface Anchoring Domains for Lactococcus lactis - Plavec, Tina Vida; Štrukelj, Borut; Berlec, Aleš (Frontiers in Microbiology, 2019)
The display of recombinant proteins on bacterial surfaces is a developing research area with a wide range of potential biotechnological applications. The lactic acid bacterium Lactococcus lactis is an attractive host for such surface display, and a promising vector for in vivo delivery of bioactive proteins. Surface-displayed recombinant proteins are usually anchored to the bacterial cell wall through anchoring domains. Here, we investigated alternatives to the commonly applied lactococcal lysine motif (LysM)-containing surface anchoring domain, the C-terminus of AcmA (cAcmA). We screened 15 anchoring domains of lactococcal or phage origins that belong to the Pfam categories LPXTG, LysM, CW_1, Cpl-7, WxL, SH3, and ChW, which can provide non-covalent or covalent binding to the cell wall. LPXTG, LysM, the duplicated CW_1 and SH3 domains promoted significant surface display of two model proteins, B domain and DARPin I07, although the display achieved was lower than that for the reference anchoring domain, cAcmA. On the other hand, the ChW-containing anchoring domain of the lactococcal phage AM12 endolysin (cAM12) demonstrated surface display comparable to that of cAcmA. The anchoring ability of cAM12 was confirmed by enabling non-covalent heterologous anchoring of the B domain on wild-type bacteria, as well as anchoring of CXCL8-binding evasin-3, which provided potential therapeutic applicability; both were displayed to an extent comparable to that of cAcmA. We have thereby demonstrated the effective use of different protein anchoring domains in L. lactis, with ChW-containing cAM12 the most promising alternative to the established approaches for surface display on L. lactis.